Acupuncture-related therapies for protracted opioid abstinence syndrome: A systematic review and meta-analysis - Lu Ding; Cui Li; Peiming Zhang; Chen Chen; Jie Zhan; Jinchun Zeng; Liming Lu (Integrative Medicine Research)
Background: An increasing amount of clinical evidence of acupuncture's effect on protracted opioid abstinence syndrome (POAS) has emerged in recent years. The aim of this study was to evaluating the evidence of efficacy of acupuncture for POAS. clinical and scientific research work. Methods: Four English-language databases (PubMed, Medline, Embase, Cochrane Libraries) and three Chinese-language databases (CNKI, WanFang and VIP Libraries) were searched, with coverage from database inception to March 31, 2022. Randomized clinical trials (RCTs) evaluating the effects of acupuncture and acupuncture-related therapies for prophylaxis or treatment of POAS were included. Data were screened and extracted independently according to pre-set tabular formats. RCT quality was assessed using risk of bias tool in the Cochrane Collaboration. The primary outcome was opiate withdrawal scale. The secondary outcomes are depression, anxiety for assessing protracted symptoms. The scores on the above scales are proportional to the severity of the symptoms. Results: Twenty-eight trials met the inclusion criteria and provided data for the meta-analysis. A total of only 3 studies (11%) were judged to be low-risk overall due to various biases in them. Acupuncture-related therapy showed statistical differences in improving protracted withdrawal symptom scores compared with sham acupuncture (5 studies, Standard mean difference (SMD), -1.85, 95% CI [-3.21, -0.50], P = 0.007), western medicine (7 studies, SMD, -0.72, 95% CI [-1.22, -0.21], P = 0.005) and no treatment (3 studies, SMD,-2.26, 95% CI [-3.82, -0.69], P = 0.005) with high heterogeneity. Conclusions: Acupuncture maybe safe and effective in relieving POAS individuals’ protracted withdrawal symptoms. However, the results of our review should be interpreted with caution because of the high risk of bias of the included trials. Study registration: The protocol of this review has been registered at PROSPERO (CRD42022335505).